Factors determining high‐sensitivity C‐reactive protein values in the Spanish population. Di@bet.es study. (7th November 2012) - Rojo‐Martínez, Gemma; Soriguer, Federico; Colomo, Natalia; Calle, Alfonso; Goday, Alberto; Bordiú, Elena; Delgado, Elías; Menéndez, Edelmiro; Ortega, Emilio; Urrutia, Inés; Girbés, Juan; Castaño, Luis; et al.
Abstract : Eur J Clin Invest 2012 Abstract: Background  Although high‐sensitivity C‐reactive protein (hs‐CRP) is currently used as a risk marker of cardiovascular disease, it has been suggested that genetic, clinical, biochemical or environmental factors could modify hs‐CRP levels. The aim of this study was to investigate sources of interindividual hs‐CRP variability in the Spanish population. Materials and methods  A representative sample of the Spanish population within the di@bet.es study was used. Study variables included a clinical and demographic structured survey, a lifestyle survey, a physical examination, plasmatic hs‐CRP and other biochemical parameters. Results  Median and interquartile range of plasma hs‐CRP values were 1·73 ± 2·75 mg/dL. Thirty per cent of the study population had hs‐CRP levels above 3 mg/dL and 38% from 1 to 3 mg/dL. Body mass index was the strongest factor associated with moderate and high hs‐CRP levels. Age, sex, waist‐to‐hip ratio, weight increase, plasma lipid levels, glucose metabolism (HOMA‐IR and abnormal glucose regulation categories), pharmacological treatment (lipid‐lowering agents, psychotropic drugs and levothyroxine), smoking, physical activity, different dietary patterns, quality of life and educational level were all significantly associated with hs‐CRP levels. Interactions were observed between variables. These interactions modulated the effect of previously described factors on hs‐CRP. Conclusions  Thirty per cent of the Spanish population have hs‐CRP levels considered to represent a cardiovascular risk. Different clinical, anthropometric, biochemical and environmental variables modulate hs‐CRP levels. In addition, multiple interactions between variables complicate the interpretation of hs‐CRP values.